An Assessment of Poverty Alleviation Measures and Sustainable Livelihood Capability of Farm Households in Rural China: A Sustainable Livelihood Approach - Fang Su; Nini Song; Nannan Ma; Altynbek Sultanaliev; Jing Ma; Bing Xue; Shah Fahad (Agriculture, 2021)
This paper aims to identify effective mechanisms for government poverty alleviation measures based on the livelihood sustainability of farm households in Southern Shaanxi province, China. The paper utilizes data from 414 farm households, collected through field observations and in-depth interviews in 24 rural communes in Qinba Mountain Area of Shaanxi province, China. Using theoretical research methods and employing the sustainable livelihood approach (SLA) framework, this paper analyzes poverty alleviation measures as well as the impact of varied capital availability on sustainable livelihood. The study shows that developing local industries and governmental financial support improve the sustainable livelihood of farmers and eradicate absolute poverty. The findings of this study further indicate that there is a positive correlation between poverty alleviation measures and natural and social capital for sustainable livelihood. The paper provides empirical and quantitative evidence on alleviation of poverty, and the findings will help improve the sustainability of livelihood capability of farming households. This study suggests impactful approaches to stabilizing mechanisms for poverty alleviation in rural areas over the longer term.